2002
DOI: 10.1046/j.1471-4159.2002.01119.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of functionally active protease‐activated receptors 1 and 2 in myenteric glia

Abstract: Protease-activated receptors (PARs) belong to the family of membrane receptors coupled to G-proteins; their presence is reported in a wide variety of cells. The object of this study was to demonstrate the presence of PAR-1 and PAR-2 in myenteric glia of the guinea pig, and to elucidate the cellular mechanisms that are triggered upon receptor activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 38 publications
(42 reference statements)
2
25
0
Order By: Relevance
“…In neocortical cultures of rat astrocytes, thrombin decreases mGluR5 protein levels (Miller et al, 1996), effects which are mimicked by the synthetic peptide SFLLRN, implying that they are dependent on the activation of the protease activated receptor (PAR) 1 (Miller et al, 1996;Vergnolle, 2004). Cultured guinea pig enteric glia express functionally active PAR-1 and -2 (Garrido et al, 2002) and levels of proteases are elevated in colitis (Vergnolle, 2004). It is possible that glial PAR-1 stimulation could account for the changes in mGluR5 receptor expression that we have observed in the IL-10 2/2 mouse.…”
Section: Mglur5 and Inflammationmentioning
confidence: 99%
“…In neocortical cultures of rat astrocytes, thrombin decreases mGluR5 protein levels (Miller et al, 1996), effects which are mimicked by the synthetic peptide SFLLRN, implying that they are dependent on the activation of the protease activated receptor (PAR) 1 (Miller et al, 1996;Vergnolle, 2004). Cultured guinea pig enteric glia express functionally active PAR-1 and -2 (Garrido et al, 2002) and levels of proteases are elevated in colitis (Vergnolle, 2004). It is possible that glial PAR-1 stimulation could account for the changes in mGluR5 receptor expression that we have observed in the IL-10 2/2 mouse.…”
Section: Mglur5 and Inflammationmentioning
confidence: 99%
“…PAR-1 is expressed on a number of cell types, including epithelium, endothelium, platelets, leukocytes, glial cells, astrocytes, and neurons [6,7]. The activation of PAR-1 leads to cell type-specific actions, including aggregation in platelets and enhancement of cytokine expression by leukocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of PAR-1 leads to cell type-specific actions, including aggregation in platelets and enhancement of cytokine expression by leukocytes. In a number of cell types, calcium release is an early consequence of PAR-1 activation [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2003) [27] showed that intercellular calcium wave propagation is a likely medium of communication for enteric glia. Moreover, myenteric glia have been shown to express functional protease-activated receptors (PARs), believed to participate in inflammation and in cellular responses to injury [11].…”
Section: Discussionmentioning
confidence: 99%
“…To confirm glial cell lineage we performed immunocytochemical staining for glial fibrillary acidic protein (GFAP) [2,11]. C6 glioma cells derived from a commercially available cell line were used as a positive control for glial cell lineage [12].…”
Section: Immunocytochemical Confirmation Of Cultured Enteroglial Cellsmentioning
confidence: 99%